Paciente de sexo femenino de 5 años de edad con desnutrición aguda. - Flores Gavilánez, Estefanía Elizabeth (2020)
The present clinical case is about a 5-year-old female patient who attended a medical consultation with the mother due to loss of appetite, decreased body weight, poor concentration, low mood and mild abdominal pain. The mother reports that the patient began to decrease her appetite 6 months ago, sometimes she had bread and coffee for breakfast and sometimes milk, and at lunch she only had chicken soup with rice and between meals, sweets, and a snack of rice with baked chicken. The nutritional evaluation is carried out with anthropometric, biochemical, clinical and dietary methods where, according to the indicator weight for age: -2 standard deviations - LOW WEIGHT FOR AGE, the indicator for height for age: 0 standard deviations - NORMAL, the indicator BMI-for-age: -3 Standard deviations –SEVERAMNETE EMACIADO and weight-for-height indicator: -3 Standard deviations –LOW WEIGHT-FOR-HEIGHT (ACUTE MALNUTRITION). The nutritional intervention is carried out with the aim of improving the nutritional status of the patient, and a diet of 1500 kilocalories hyperprotein is established distributed in 5 meal times and nutritional food education, the control is carried out where weight gain is observed in 3 months considerably and their nutritional status is improving, in this way it is concluded that nutritional intervention, compliance with the dietary plan and food education favors weight gain and treat acute malnutrition.